An economic theorist’s book of tales : - Akerlof, George A. (Cambridge University Press, 1984)
These essays explore what happens when a skilful economist makes unconventional assumptions. These essays are substantively and stylistically novel because they break these taboos and bring new assumptions into economic theory. The papers apply this adventurous approach to a wide range of issues - from insurance markets and trade in underdeveloped countries to unemployment and discrimination. Some of the essays derive the implications for economic markets of costly asymmetric information. Others explore the findings of other social sciences such as anthropology, psychology and sociology